A class of mixed integrable models - Gomes, J. F. [UNESP]; de Melo, G. R. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Iop Publishing Ltd, 2009)
The algebraic structure of the integrable mixed mKdV/sinh-Gordon model is discussed and extended to the AKNS/Lund-Regge model and to its corresponding supersymmetric versions. The integrability of the models is guaranteed from the zero curvature representation and some soliton solutions are discussed.